Assessing the challenges facing Nomadic Education Programme implementation in Kwara State, Nigeria - Sadiq Toyin Kayode (Universitas Negeri Semarang, 2025)
This paper examined the challenges affecting the implementation of the nomadic education programme in Kwara State, Nigeria. A qualitative research approach was adopted, and 378 of the 1,680 selected respondents participated in the study. Data were collected using a self-designed questionnaire. Descriptive statistics (mean scores and standard deviations) were used to address the research questions, and one hypothesis was tested using the Pearson product–moment correlation at the 0.05 significance level. Findings revealed that the constraints to implementing the nomadic education programme in Kwara State were severe (x̅ = 2.73 ± 0.76) across the education centres. In addition, the availability of educational infrastructure (F = 87.325; p = 0.000), curriculum implementation (F = 36.900; p = 0.000), availability of trained facilitators (F = 26.822; p = 0.000), and the overall constraints to nomadic education (F = 83.212; p = 0.000) significantly influenced nomads’ participation in nomadic education programmes in the study area.